Criterios jurisprudenciales de la Corte Suprema sobre el despido nulo - Toyama Miyagusuku, Jorge; Neyra Salazar, Carole Ivonne (Pontificia Universidad Católica del Perú, 2016)
In this article, the authors explain some notions about job security and some general aspects of the nullity of the dismissal (proof of the dismissal null and its causes). Also, they explain the judicial criteria on the nullity of dismissal that have been issued through cassation rulings by the Supreme Court. Among these criteria are union membership or participation in union activities, filing a complaint or participation in processes against the employer, discrimination, and pregnancy.

En el presente artículo, los autores explican algunas nociones acerca de la estabilidad laboral y algunos aspectos generales de la nulidad del despido (la prueba del despido nulo y sus causales). Asimismo, posteriormente explican los criterios jurisprudenciales sobre la nulidad del despido que han sido emitidos a través de sentencias de casación por la Corte Suprema. Dentro de estos criterios se encuentran la afiliación a un sindicato o la participación en actividades sindicales, la presentación de una queja o la participación en un proceso contra el empleador, la discriminación, y el embarazo.
Jurisprudential criteria of the Supreme Court about the dismissal null
Keywords: Dismissal Null; Job Security; Supreme Court; Union Membership; Process Against The Employer; Discrimination; Pregnancy; Despido Nulo; Estabilidad Laboral; Corte Suprema; Afiliación Sindical; Proceso Contra El Empleador; Discriminación; Embarazo; https://purl.org/pe-repo/ocde/ford#5.05.00